The comparison of surface roughness value of microfilled and nano particle composite restoration that polish using rubber cups - Gita Retyoningrum; Rizki Yuli Amanda; HD Adhita Dharsono; Renny Febrida (Padjadjaran Journal of Dentistry, 2009)
Surface roughness composite restoration can decrease aesthetic aspect of composite restoration and facilitated bacterial retention. It can affect periodontal disease and recurrent caries. Polishing is a process to obtain a smooth and glossy surface of restoration. Rubber cups is one of polishing instrument that frequently used to get a smooth, glossy and aesthetic surface of restoration. The specimen was micro filled (3M ESPE Z100TM Restorative, St. Paul) and nano particle (3M ESPE Z350TM Restorative, St. Paul) composite resin blocks sized 5x5x2 mm. Each of composite consists of ten specimens that polished with rubber cups for 30 seconds at 3500 rpm. Surface roughness was measured five times for each specimen by using surface roughness tester. Average Ra value of micro filled was 0.22 μm and Ra value of nano particle was 0.25 μm. Data were analyzed by using independent t-test at α 0.05 significance level and showed statistically significant differences. The conclusion of this experiment showed that surface roughness value of micro filled composite resin was smaller than nano particle composite resin restoration. A small amount of filler particle (50.6% wt) made micro filled easier to polish and made a smooth surface restoration. Nano particle composition has more filler particle amount (78.5% wt), and hard zirconia filler that difficult to polish than silica colloidal filler in microfilled composite resin.